Law of international trade : cross-border commercial transactions - Chuah, Jason (London : Sweet & Maxwell, 2013)
Presenting a comprehensive treatment of all key aspects of private international trade law, this book demonstrates to the reader how international trade law operates in its political, economic and business contexts.
Introduction and context -- International sale of goods -- Terms under the Sale of Goods Act 1979 -- Remedies in International Sales -- The Vienna Convention on Contracts for the International Sale of Goods -- Bills of Lading -- Charterparties and Common Law Principles Applicable to Carriage of Goods by Sea -- International Conventions on Carriage of Goods by Sea -- Carriage of Goods by Air, Road and Rail -- Marine Insuranse for Cargo -- Paymetn and finance for international trade -- Civil and commercial jurisdiction -- Choice of law for contractual and non-contractual obligations -- Recognising and enforcing foreign awards -- Alternative dispute resolution.
Previous edition: 2009.
Includes bibliographical references and index.
Keywords: Foreign trade regulation; Commercial law; Commercial law; Foreign trade regulation; Internationales Handelsrecht; 2; 2; Utrikeshandel -- juridik och lagstiftning; Law; Law; England; Wales